«Haremos de Valencia una Atenas» - Jordane Fauvey (Edicions UIB, 2021)
This article deals with the influence of Ancient Greek culture on Sorolla’s beach painting still strongly associated with his name nowadays. It also tells how the painter studied Greek art during his early training thus becoming greatly enthusiastic about it. According to Fauvey, this influence made a decisive mark on Sorolla’s paintings from «La vuelta de la pesca» (1894) (Return from fishing). On the beach, Sorolla came up with a genre based on his knowledge of Ancient Greek culture to show Mediterranean ties between Athens and Valencia. Sorolla’s beach would not become naturalist but mythical.